Ways of industrial-innovative modernization of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The article defines the means and objectives of national economic development processes, which are realized through the provision of socio-economic development. It is based on the main provisions of RK President Nursultan Nazarbayev to the people of Kazakhstan, according to which our country should develop in line with global economic trends and directions
Keywords: industrial modernization and innovation; factors and the socio-economic development of Kazakhstan; infrastructure triad trajectory successful modernization